Closing gaps: linking elements that control stomatal movement. Issue 1 (6th May 2014) - Kollist, Hannes; Nuhkat, Maris; Roelfsema, M. Rob G.
Summary: Stomata are an attractive experimental system in plant biology, because the responses of guard cells to environmental signals can be directly linked to changes in the aperture of stomatal pores. In this review, the mechanics of stomatal movement are discussed in relation to ion transport in guard cells. Emphasis is placed on the ion pumps, transporters, and channels in the plasma membrane, as well as in the vacuolar membrane. The biophysical properties of transport proteins for H +, K +, Ca 2+, and anions are discussed and related to their function in guard cells during stomatal movements. Guard cell signaling pathways for ABA, CO2, ozone, microbe‐associated molecular patterns (MAMPs) and blue light are presented. Special attention is given to the regulation of the slow anion channel (SLAC) and SLAC homolog (SLAH)‐type anion channels by the ABA signalosome. Over the last decade, several knowledge gaps in the regulation of ion transport in guard cells have been closed. The current state of knowledge is an excellent starting point for tackling important open questions concerning stress tolerance in plants.   Contents     Summary 44 I. Introduction 44 II. Mechanics of stomatal movement 45 III. Guard cells – specialists in ion transport 46 IV. Regulation of stomatal movement 53 V. Outlook 56   Acknowledgements 57   References 57